Co-habiter avec les images - Pierre-Olivier Dittmar (Images Re-Vues)
How can we think of "co-habitation" with images, i.e. the co-presence of individuals or groups, and images, in living spaces, where we eat and sleep? This programmatic article aims to launch new avenues and open up a field of research dedicated to the analysis of images in the domestic space, based on a series of questions and migrations that concern the western space between the 13th and 21st centuries.